2020
DOI: 10.4252/wjsc.v12.i2.123
|View full text |Cite
|
Sign up to set email alerts
|

Clonal isolation of endothelial colony-forming cells from early gestation chorionic villi of human placenta for fetal tissue regeneration

Abstract: BACKGROUND Endothelial colony-forming cells (ECFCs) have been implicated in the process of vascularization, which includes vasculogenesis and angiogenesis. Vasculogenesis is a de novo formation of blood vessels, and is an essential physiological process that occurs during embryonic development and tissue regeneration. Angiogenesis is the growth of new capillaries from pre-existing blood vessels, which is observed both prenatally and postnatally. The placenta is an organ composed of a variety of fetal-derived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Additionally, MSCs have also demonstrated the ability to regulate the immune system through multiple independent pathways [ 38 ] which may facilitate wound healing. On the other hand, EPCs can engraft and become part of the neovasculature if the environment is permissive [ [39] , [40] , [41] ]. EPCs could also secrete angiogenic growth factors that may facilitate wound healing [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MSCs have also demonstrated the ability to regulate the immune system through multiple independent pathways [ 38 ] which may facilitate wound healing. On the other hand, EPCs can engraft and become part of the neovasculature if the environment is permissive [ [39] , [40] , [41] ]. EPCs could also secrete angiogenic growth factors that may facilitate wound healing [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, CD105 and CD146 expression was lower than that observed in the control group; CD105 and CD146 expression was decreased from 99.37 to 58.41% and from 97.60 to 69.75%, respectively. CD146 and CD105 are both primarily endothelial cell markers associated with vascular endothelial cell activity and angiogenesis ( Nakashima et al, 2009 ; Gao et al, 2020 ). These results again suggested that d-DPSCs cultured in 10% FBS α-MEM had the ability to restore partly their stemness but had less capacity for angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…All lentiviral constructs were generated at the UC Davis Institute for Regenerative Cures (IRC) Vector Core. To track the cell fate and behavior in vitro and in vivo , ECFCs were transduced with the pCCLc-MNDU3-LUC-PGK-EGFP-WPRE vector as previously described ( Kumar et al, 2018 ; Gao et al, 2019 , 2020 ; Rose et al, 2020 ). Transduction was performed in transduction medium consisting of DMEM high glucose (HyClone), 10% FBS (HyClone), and 8 μg/mL protamine sulfate (MP Biomedicals) for 6 h. The vectors were transduced at a multiplicity of infection (MOI) of 10.…”
Section: Methodsmentioning
confidence: 99%